Radiation exposure levels in close proximity to therapeutic patients treated for thyroid carcinoma with high dose I-131 (Bangladesh Journal of Nuclear Medicine, 2015)
High dose I-131 therapy is administered to thyroid cancer patients after thyroidectomy. In the treatment process when a radiopharmaceutical is administered to patients, they become a mobile source of radiation. After the treatment, contamination may arise from large amount of activity, which is excreted during the period of hospitalization. To reduce the rate of exposure it is essential to monitor workplace. This study determines the rate of radiation exposure in the room where the patient stays during the period of hospitalization as well as the adjacent rooms and surrounding areas. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22491 Bangladesh J. Nuclear Med. 17(1): 50-54, January 2014